2008
DOI: 10.1038/ng.220
|View full text |Cite
|
Sign up to set email alerts
|

Control of rice grain-filling and yield by a gene with a potential signature of domestication

Abstract: Grain-filling, an important trait that contributes greatly to grain weight, is regulated by quantitative trait loci and is associated with crop domestication syndrome. However, the genes and underlying molecular mechanisms controlling crop grain-filling remain elusive. Here we report the isolation and functional analysis of the rice GIF1 (GRAIN INCOMPLETE FILLING 1) gene that encodes a cell-wall invertase required for carbon partitioning during early grain-filling. The cultivated GIF1 gene shows a restricted e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
506
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 718 publications
(528 citation statements)
references
References 29 publications
16
506
0
6
Order By: Relevance
“…Extensive studies have shown essential roles of CWIN in seed filling, probably through regulating Suc unloading and the establishment and maintenance of sink strength (Cheng et al, 1996;Weber et al, 1996;Wang et al, 2008;Jin et al, 2009;Zanor et al, 2009). However, it remains largely unknown how CWIN exerts its regulation early in seed development .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have shown essential roles of CWIN in seed filling, probably through regulating Suc unloading and the establishment and maintenance of sink strength (Cheng et al, 1996;Weber et al, 1996;Wang et al, 2008;Jin et al, 2009;Zanor et al, 2009). However, it remains largely unknown how CWIN exerts its regulation early in seed development .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CWINs are central to phloem unloading and carbon partitioning, especially in cellular sites lacking symplasmic (plasmodesmal) connections (Patrick and Offler, 2001;Weschke et al, 2003). A positive correlation between CWIN activity and seed development has been observed in maize (Zea mays; Cheng et al, 1996;Vilhar et al, 2002;Chourey et al, 2006), faba bean (Vicia faba; Weber et al, 1995Weber et al, , 1996, barley (Hordeum vulgare; Weschke et al, 2003;Sreenivasulu et al, 2004), rice (Oryza sativa; Hirose et al, 2002;Wang et al, 2008), and tomato (Solanum lycopersicum; Zanor et al, 2009). With an exception in tobacco (Nicotiana tabacum; Tomlinson et al, 2004), high and low Glc-to-Suc ratios generally favor cell division or promote cell differentiation, respectively, during seed development (for review, see Weber et al, 2005).…”
mentioning
confidence: 99%
“…Several genes related to rice domestication, including sh4, qSH1, PLOG1, qSW5, GIF1, and Rc, have been cloned and the corresponding causal FNPs have also been identified (Konishi et al, 2006;Li et al, 2006;Sweeney et al, 2007;Jin et al, 2008;Shomura et al, 2008;Tan et al, 2008;Wang et al, 2008). Among them, a 14-bp deletion within the Rc gene, which induced a premature stop codon, resulted in the change of pericarp color from red to white.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown much progress on exploring the mechanism for regulation of yield potential, plant height, and flowering time in rice. Some genes regulating the rice yield trait have already been identified (Li et al, 2003;Ashikari et al, 2005;Fan et al, 2006;Song et al, 2007;Shomura et al, 2008;Wang et al, 2008;Weng et al, 2008). The control of rice plant height is mostly related to the synthesis and regulation of the phytohormone, such as GA and brassinolide (Ashikari et al, 1999;Yamamuroa et al, 2000;Honga et al, 2003;Sasaki et al, 2002Sasaki et al, , 2003Itoh et al, 2004;Tanabe et al, 2005).…”
mentioning
confidence: 99%